2016
DOI: 10.1590/1807-1929/agriambi.v20n6p557-563
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of castor bean cultivars under salt stress

Abstract: A B S T R A C TThis study aimed to evaluate the tolerance of castor bean cultivars under salt stress during the initial growth stage. The experiment was set in randomized blocks, in a 5 x 4 factorial scheme, resulting in 20 treatments, 5 salinity levels (0.6-control, 1.2, 1.8, 2.4 and 3.0 dS m -1 ) and 4 castor bean cultivars (BRS Energy, LA Guarani, BRS Gabriela and IAC 028)] with 3 replicates. At 30 days after sowing, plants were evaluated for growth, dry matter accumulation and salt tolerance. Increased sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Nobre et al (2013) also observed that ECw negatively influenced plant height of castor bean BRS Energy to 67 DAS, which found that there were decreases in the order of 6.22% (16.72 cm) in AP per unit increased in ECw. Sá et al (2016) found a decrease of 3.73 cm in plant height per unit increased in ECw.…”
Section: Resultsmentioning
confidence: 88%
“…Nobre et al (2013) also observed that ECw negatively influenced plant height of castor bean BRS Energy to 67 DAS, which found that there were decreases in the order of 6.22% (16.72 cm) in AP per unit increased in ECw. Sá et al (2016) found a decrease of 3.73 cm in plant height per unit increased in ECw.…”
Section: Resultsmentioning
confidence: 88%
“…Sá et al (2016) found that increase in salinity levels caused linear reductions in salt tolerance index of all the varieties of castor bean, with 63.82% reductions to cultivate LA Guarani, 79.80, 75.51 and 77.91% for BRS Energy cultivars BRS Gabriela and IAC 028, respectively. Graciano et al (2011) observed that peanut cv.…”
Section: Resultsmentioning
confidence: 95%
“…Several studies have shown the harmful effects of saline irrigation water on the peanut crop (Correia et al, 2009;Graciano et al;2011;Santos et al, 2012;Sousa et al, 2012) and other oilseeds like castor bean (Nobre et al, 2013Santos et al, 2013;Lima et al, 2014;Sá et al, 2016;), jatropha , sunflower (Morais et al, 2011;Maciel et al, 2012), and legumes like beans (Neves et al, 2008;Garcia et al, 2010;Bezerra et al, 2010;Aydin et al, 2012). However, most studies have not shown the effect of biofertilizers as a way to mitigate the effects of salt stress on peanuts, mainly in the reproductive phase.…”
Section: Introductionmentioning
confidence: 99%
“…BRS-Energia) seeds used in this research were provided by EMBRAPA, Campina Grande, Paraíba, Brazil. According to Sá et al (2016), this cultivar is more salt tolerant than other commercial cultivars. The research was divided into three stages: (i) characterization of the effects of salt stress on seed germination and seedling establishment, (ii) selection of beneficial priming techniques for castor bean seeds, and (iii) evaluation of the action of the best castor bean priming techniques against salt stress.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 98%